КОМП’ЮТЕРНІ ІМІТАЦІЙНІ МОДЕЛІ ТА ОСВІТА (Педагогіка вищої та середньої школи, 2007)
The computer is with just cause possible to consider the integral part of the scholastic process. The computer simulation models are an important facility, which increases the possibility of the active education. Using of simulation modeling in education must, first of all, have a didactic motivation, and justified only in that event if it is oriented on achievement determined pedagogical result.